Case Report: The potential association with polyglandular autoimmune syndrome in a dog following long-term oclacitinib therapy - Lee, Kwang-Sup; Yoon, Jun-Won; Dan, Tae-Jung; Lim, Sang-Min; Jeon, Hee-Jung; Kang, Mi-Ae; Nam, Chan-Sik; Park, Hee-Myung (Frontiers in Veterinary Science, 2025)
A 12-year-old spayed female Maltese dog had been receiving oclacitinib, a Janus kinase (JAK) inhibitor, for 7 years to manage chronic pruritus due to atopic dermatitis. During this treatment, the dog was diagnosed with primary hypoadrenocorticism and hypothyroidism based on history, physical examination, and hormonal analysis. This case was initially suspected to be polyglandular autoimmune syndrome (PAS) based on long-term treatment of oclacitinib. To confirm the diagnosis of PAS, the presence of autoantibodies was tested. 21-hydroxylase autoantibodies (21-OHAb) were detected, but negative for thyroglobulin autoantibodies (TgAA). Considering the potential of oclacitinib to induce autoimmune diseases, we examined to identify the association of interleukin-10 (IL-10) in PAS of the dog. This case suggests a potential association between prolonged oclacitinib administration and the development of PAS in a dog. Regular hormonal monitoring and careful dose adjustments of oclacitinib during long-term therapy of atopic dermatitis are recommended to minimize the risk of autoimmune disease development. To the best of our knowledge, this is the first case report suggesting that PAS could be induced by oclacitinib.